Study on channel propagation of cellular-to-UAV in a typical sub-urban environment in Malaysia - Mohd Kamal N.L. (Science and Engineering Research Support Society, 2023)
This paper presents the investigation on the usability of cellular network infrastructure to be used for Unmanned Aerial Vehicle (UAV) platform. The current infrastructure is optimized for user on ground, thus it is anticipated that the connectivity is reduced if the user is located higher than the ground level. The field experiment is conducted by flying the Unmanned Aerial Vehicle (UAV) vertically and the channel propagation properties which in this work is quantified by the Received Signal Strength (RSS) is recorded. Received signal strength values measured at the UAV are compared with that obtained from ground measurement for affirmation of UAV compatibility with the existing cellular network. As environmental conditions play a significant role in determining the signal propagation, in this study, a sub-urban location is selected where the surrounding areas comprise of hilly areas with palm oil plantation and low rise building within the vicinity. The channel propagation of cellular-to-UAV is investigated for four different network providers in Malaysia. Results have shown that there is significant variation in aerial performance among different network providers and that a particular network provider can be selected which fulfill the requirement of the desired UAV application. 2020 SERSC.